2020
DOI: 10.1002/ajmg.a.61934
|View full text |Cite
|
Sign up to set email alerts
|

A new case of osteogenesis imperfecta type VIII and retinal detachment

Abstract: Osteogenesis imperfecta (OI) type VIII (OMIM: 610915) is a rare autosomal recessive disorder characterized by white sclerae, severe growth deficiency, and bone fragility. This condition results from pathogenic variants of P3H1, a gene that codes for P3H1, an important protein involved in the prolyl‐3‐hydroxylation complex required for collagen type I folding. Here, we described a woman with OI type VIII due to a homozygous mutation of c.1914+1G>C (NM_001243246.1) in P3H1 and retinal detachment. We compared our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(19 reference statements)
0
1
1
Order By: Relevance
“…12 Furthermore, de Souza et al reported retinal detachment in a 28-year-old OI type VIII case with a similar mutation (c.1914 + 1G>C (NM_001243246.1)). 13 However, fundoscopic examinations of our cases were found to be normal.…”
Section: Discussioncontrasting
confidence: 46%
“…12 Furthermore, de Souza et al reported retinal detachment in a 28-year-old OI type VIII case with a similar mutation (c.1914 + 1G>C (NM_001243246.1)). 13 However, fundoscopic examinations of our cases were found to be normal.…”
Section: Discussioncontrasting
confidence: 46%
“…A similar case of type VIII OI due to a homozygous mutation of c.1914+1G>C (NM_001243246.1) in P3H1 exhibited retinal detachment, emphasising the need for fundoscopic examination as part of a multidisciplinary approach 4…”
Section: Discussionmentioning
confidence: 99%
“…3 A similar case of type VIII OI due to a homozygous mutation of c.1914+1G>C (NM_001243246.1) in P3H1 exhibited retinal detachment, emphasising the need for fundoscopic examination as part of a multidisciplinary approach. 4 The variant P3H1, and variant coordinate 1095C>G p. (Tyr365*), create a premature stop codon. 5 6 Pathogenic P3H1 variants are causative for autosomal-recessive OI type VIII.…”
Section: Discussionmentioning
confidence: 99%
“…Para duplicação, espera-se três cópias na amostra e duas no controle (razão de 0,6) enquanto, para deleção espera-se uma cópia na amostra para duas cópias de controle (razão de 0,3). PALLOS et al, 2001;REIS et al, 2005;BARBIRATO et al, 2009;ADUR et al, 2013;KANETO et al, 2014;MINILLO et al, 2014;BRIZOLA et al, 2015;FERNANDES et al, 2020;TRANCOZO et al, 2019;BARBIRATO et al, 2015;BARBIRATO et al, 2016;MOOSA et al, 2019;DE SOUZA et al, 2021;AMORIM et al, 2022;NAPOLEÃO et al, 2022;HOLTZ et al,2023), com destaque para os seguintes pontos:…”
Section: Análise De Cnvcaso Hipofosfatasiaunclassified